Między Herostratesem a Czarną wiosną. O tradycji literackiej u progu dwudziestolecia międzywojennego (na lekcjach języka polskiego w szkole średniej) - Mazur, Elżbieta (Dydaktyka Polonistyczna, 2018)
The article focuses on the role of literary tradition, particularly linked to Romanticism, in the poetry of the Skamandrites. The author discusses examples of lyric poetry created after 1918 and manifesting varied approaches to tradition, i.e. rejection, continuation or negation of the key tradition, as well as the attitude of poetry towards history. She also points to the problem of tradition in secondary-level Polish language education and to the teaching concepts designed to develop students’ ability to understand and identify traditions.